GROWING GONDWANA AND RETHINKING RODINIA: A PALEOMAGNETIC PERSPECTIVE - Meert J.G. (My University, 2001)
The formation of Gondwana during the late Neoproterozoic to early Cambrian times (550-530 Ma) was traditionally viewed as the welding of two, more or less contiguous, Proterozoic continental masses called East and West Gondwana. The notion of a united West Gondwana is no longer tenable as a wealth of geochronologic and structural data indicate major orogenesis amongst its constituent cratons during the final stages of greater Gondwana assembly. The idea that East Gondwana may also have formed through the amalgamation of a collage of cratonic nuclei during the Cambrian is controversial. Recent paleomagnetic, geochronologic and structural data from elements of East Gondwana indicate that its formation may have extended well into Cambrian time. Thus, the terms ‘East’ and ‘West’ Gondwana may be relegated to convenient geographical terms rather than any connotation of tectonic coherence during the Proterozoic. In addition, the paleomagnetic data also challenge the conventional views of the Neoproterozoic supercontinent Rodinia and the SWEAT fit. Alternative variants including Protopangea and AUSWUS are not supported by paleomagnetic data during the interval 800–700 Ma.
Keywords: Neoproterozoic; Proterozoic; Cambrian; Докембрий::Протерозой; Докембрий::Протерозой::Неопротерозойская; Paleozoic::Cambrian; Precambrian::Proterozoic; Precambrian::Proterozoic::Neoproterozoic; Палеозой::Кембрийская